A Solution Approach to the Challenge of Digitalization in Islamic Boarding Schools: Combining Tradition with Technology - Lu’at Happyana; Muh. Imam Khaudli; Fina Zaidatul Istiqomah (Quality Assurance Institute (LPM) State Islamic University Walisongo Semarang, 2024)
This research investigates technology integration in Islamic boarding school education at the Darussalam Islamic Boarding School Blokagung, Banyuwangi. The aim is to understand the implementation of social media for da'wah and education, technology-based assessment systems, and library digitalization in the context of Islamic boarding schools. The research method used is a qualitative approach with a case study at the Darussalam Islamic Boarding School, Blokagung, involving teaching staff, Islamic boarding school managers and students as the main informants. Data collection techniques will be collected through interviews and participatory observation in daily activities at the Darussalam Islamic Boarding School Blokagung. The research results show that integrating technology with traditional values ​​can improve the quality of education and expand the positive impact of Islamic education in Islamic boarding schools.